EXPLORING DRIVERS AND BARRIERS TO CIRCULAR ECONOMY ADOPTION AMONG SMES: EVIDENCE FROM THE TWO4C PROJECT - Raden Ajeng Arimbi Dyah Lokashinta Wibisono; Agung Juliarto; Kees Tesselhof; Frank Gruben (Diponegoro Journal of Accounting, 2025)
Small and Medium Enterprises (SMEs) play a pivotal role in the transition toward a circular economy (CE), yet they often face significant barriers in adopting circular practices. This research explores the main drivers and barriers influencing CE adoption among SMEs engaged in the TWO4C project, a Dutch–German cross-border initiative aimed at accelerating circular transformation. Using survey data from SMEs in construction, electronics, plastics, metal, and wood industries, the study applies a descriptive quantitative approach.Findings reveal that internal innovation culture, employee empowerment, and leadership support serve as critical drivers, while traditional mindsets, lack of knowledge, and operational inertia remain significant barriers. Participation in the TWO4C project provides indirect benefits by fostering peer learning, knowledge exchange, and collaboration across borders.The study contributes to the literature by integrating four theoretical perspectives—Institutional Theory, Resource-Based View (RBV), Transition Management (TM), and Organizational Learning (OL)—to explain CE adoption dynamics. Practical recommendations are provided for SMEs, policymakers, and support institutions to strengthen innovation capabilities, shift cultural mindsets, and leverage cross-border collaboration to accelerate circular transitions.